Regional Apparatus Resource Readiness Through Digitalization of Public Programs and Services Towards Smart City (Study at Regional Education and Training Personnel Agency South Halmahera Regency ) - Haryono A. Hi. Gani; Ali Lating; Syarifuddin Usman (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2023)
Nowadays, almost all cities in every developed country have implemented the Smart City concept by utilizing information and communication technology (ICT) to be able to control all the resources in the city. Indonesia is one of the countries implementing this smart city, including DKI Jakarta, Surabaya, Bandung, Yogyakarta and Makassar. In the government program on